Study of Tridax procumbens L. Extract on SOD and MDA levels in Cingarette Smoke Exposed Rats - setiawan, haris; Azali, Aulia Syafadilla; Wardani, Diah Kartika; Nurazizah, Intan Faya; Nurrohiim, Annisaa’ (Universitas Ahmad Dahlan, 2025)
Cigarette smoke is a source of free radicals that can damage cells and tissues of the respiratory tract. Tridax procumbens L. has potential as an antioxidant because it contains flavonoids that play a role in counteracting free radicals. The study aims to determine the potential of Tridax procumbens L. as a source of antioxidants against SOD and MDA levels in Wistar rats exposed to cigarette smoke. The study used Wistar rats (25 heads) with 5 treatments consisting of K (aquadest), KN (exposed to cigarette smoke), P1 (exposed to cigarette smoke and given 100 mg/kg BW extract), P2 (exposed to cigarette smoke and given 200 mg/kg BW extract), and P3 (exposed to cigarette smoke and given 300 mg/kg BW extract). Extract administration was carried out on days 1-21 and cigarette smoke exposure was carried out on days 8-21. Parameters observed consisted of flavonoid content test (by KLT method, total flavonoid content, total phenolic content), body weight, SOD levels (whole blood method), and MDA levels (TBARs method). Data were analyzed by one-way ANOVA test (P<0.05) followed by Duncan post hoc test. The results showed that Tridax procumbens L. contains flavonoids with an Rf value of 0.23. Body weight showed no significant difference (P>0.05), but SOD and MDA levels were different between treatments (P<0.05) with the most optimum dose of 300 mg/kg BW. The conclusion shows that a dose of 300 mg/kg BW of ethanol extract of Tridax procumbens L. can act as a natural antioxidant from exposure to cigarette smoke in vitro.